The Influence of Professional Competence and Working Environment to The Teachers Performance of The Economic Teachers in Senior High School At Pemalang Regency Through Their Working Motivation - Pujiastuti, Sri; Murwatiningsih, Murwatiningsih; Rozi, Fahrur (Universitas Negeri Semarang, 2017)
This study aims to analyze the influence of professional competence on the performance of economic teachers, professional competence on the performance of economic teachers through work motivation, work environment on teacher economic performance, work environment on teacher economic performance through work motivation, and work motivation on teacher economic performance. Analytical techniques used descriptive analysis and path analysis. The results showed that there is a positive and significant influence of professional competence on teacher economic performance of 17.8%. Professional competence on teacher economy performance through work motivation is 28%. Working environment on teacher economics performance amounted to 41.2%. Work environment on teacher economy performance through work motivation of 77.7%. Motivation of work on teacher economic performance equal to 48,2%. The conclusion of this study is the teacher performance is getting better when the professional competence of a teacher is better, the total value is greater than the direct influence of professional competence to the economic teachers performance, the better working environment makes the better teacher economic performance, the total value is greater than the direct influence of the work environment to the economic teacher performance, and the more economic teachers have a high work motivation, the better their performance.